Microstructure and mechanical behaviour of cold metal transfer welded Mg/Al dissimilar joint using wire AZ31 as filler metal. (19th May 2017) - Wang, P.; Hu, S. S.; Shen, J. Q.; Liang, Y.
ABSTRACT: Mg/Al dissimilar butt joint was produced by modified cold metal transfer process using wire AZ31 as filler metal. The energy input characteristics and the microstructure and mechanical behaviour of the joint were investigated. Microstructural analysis shows that a diffusion Mg–Al intermetallic compounds interface layer formed along the weld boundary near Al substrate. The interface layer consisted of three intermediate layers from Al substrate to weld metal: Mg2 Al3 layer, Mg17 Al12 layer and Mg17 Al12 + α -Mg solid solution eutectic layer. The tensile strength of the welded joint was 38.4 MPa, which was fairly dependent on the lowest strength of the three intermediate layers. The brittle fracture occurred primarily within the thinnest Mg2 Al3 intermediate layer adjacent to Al substrate.